2014
DOI: 10.1073/pnas.1402391111
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of S-region hypermutation and class-switch recombination by noncanonical functions of uracil DNA glycosylase

Abstract: Activation-induced cytidine deaminase (AID) is essential to classswitch recombination (CSR) and somatic hypermutation (SHM) in both V region SHM and S region SHM (s-SHM). Uracil DNA glycosylase (UNG), a member of the base excision repair (BER) complex, is required for CSR. Strikingly, however, UNG deficiency causes augmentation of SHM, suggesting involvement of distinct functions of UNG in SHM and CSR. Here, we show that noncanonical scaffold functions of UNG regulate s-SHM negatively and CSR positively. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 60 publications
2
35
1
Order By: Relevance
“…More importantly, APE1's endonuclease activity is not required for the AIDinduced DNA cleavage, in parallel with the findings that UNG is dispensable for the DNA cleavage step during SHM (56,57) and CSR (39,58). Recently, we reported that UNG enhances AIDdependent S-S synapse formation by recruiting p53-binding protein 1 and DNA-dependent protein kinase, catalytic subunit (49). We provide the evidence indicating that APE1 processes the broken ends of S-region DNA for the binding of Ku80 and mediates efficient S-S synapse formation during CSR.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…More importantly, APE1's endonuclease activity is not required for the AIDinduced DNA cleavage, in parallel with the findings that UNG is dispensable for the DNA cleavage step during SHM (56,57) and CSR (39,58). Recently, we reported that UNG enhances AIDdependent S-S synapse formation by recruiting p53-binding protein 1 and DNA-dependent protein kinase, catalytic subunit (49). We provide the evidence indicating that APE1 processes the broken ends of S-region DNA for the binding of Ku80 and mediates efficient S-S synapse formation during CSR.…”
Section: Discussionsupporting
confidence: 65%
“…UNG suppresses SHM by recruiting faithful BER pathway components at cleaved DNA loci, with competition against error-prone polymerases (49). In contrast, APE1 is not involved in the correct repair after cleavage during SHM because SHM occurs similarly between vector and WT transfectants of Ape1-null CH12F3-2A cells.…”
Section: Discussionmentioning
confidence: 99%
“…In CSR, AID is targeted to an upstream (donor) S and a downstream (acceptor) S regions by 14-3-3 adaptors, which display high affinities for 5′-AGCT-3′ repeats, as recurring in all S regions, as well as for H3K9acS10ph histone posttranslational modifications, as induced specifically in the donor and acceptor S regions – these S regions also undergo germline I H -S-C H transcription initiated upon activation of their respective upstream intervening I H promoter (4, 5). High densities of deoxyuracils, as generated through AID-mediated DNA deamination, are processed by uracil DNA glycosylase (Ung) recruited by Rev1 (6-8), leading to the generation of S region (DSBs), which are obligatory CSR intermediates. Repair of such DSBs results in looping out of the intervening DNA as an S circle, formation of a S-S junction and juxtaposition of the expressed V H DJ H DNA to the downstream C H DNA.…”
Section: Introductionmentioning
confidence: 99%
“…AID induces DNA breaks at the variable (V) and switch (S) regions during SHM and CSR, respectively. Most of the mutations produced during SHM are introduced by errorprone DNA synthesis during single-strand break (SSB) repair (3,4). In contrast, CSR requires the conversion of SSBs to doublestrand breaks (DSBs), followed by recombination between two DSB ends located in the donor and acceptor S regions (5,6).…”
mentioning
confidence: 99%